Mędrzec – ideał człowieka poszukującego mądrości (Syr 14,20 – 15,10). Część I: Działanie mędrca (Syr 14,20-27) - Piwowar, Andrzej (The Biblical Annals, 2016)
In Sir 14:20–15:10 Sirach continues his teachings concerning the acquisition of wisdom (cf. 1:1-10; 4:16-19 and 6:18-37) (the exegetico-theological analysis conducted in this article is based on the Greek version of the fragment). In the pericope the author presents the sage as a model and an example to follow for all those who wish to acquire wisdom. The pericope under analysis here comprises two parts. The present article focuses on the first one (14:20-27), in which Sirach concentrates on the actions the sage undertakes to acquire wisdom. The second section (15:1-10) in turn makes use of three metaphors to present the actions of wisdom throughout the process of a man’s search for it. The first part of the pericope (14:20-27) can be further divided into three sections. In the first one (14:20-21) Sirach praises the man who seeks wisdom, emphasizing his intellectual engagement (in the form of contemplating or pondering) as the basis for reaching the aim and finding wisdom. The second part (14:22-25) presents the actions aimed at acquiring wisdom with the use of three metaphors: the first is that of hunting (14:22), and the second – that of spying (14:23), even though verses 21:23-24 include a prohibition and a harsh reprimand against peeping or eavesdropping. The third metaphor, the most developed of all three, refers to camping next to wisdom (14:24-25). In the final section of part one (14:26-27) Sirach presents the promises made to those who strive to acquire wisdom, namely protection from danger and living close to wisdom.